A variable forgetting factor RLS adaptive filtering algorithm - Junfeng Wang (Proceedings, 2009 3rd IEEE International Symposium on Microwave, Antenna, Propagation and EMC Technologies for Wireless Communications : 27-29 October 2009, Beijing, China, 2009)
The recursive least squares algorithm (RLS) is realized in MATLAB. Simulation results show that forgetting factor influences the algorithm convergence and stability, which will significantly affect the performance of adaptive filter. Therefore, a variable forgetting factor RLS algorithm is presented in this paper. Simulation results show that the convergence and stability of the variable forgetting factor RLS algorithm (VRLS) are superior to ordinary RLS algorithm. Finally, the RLS algorithm is applied in channel equalization in low SNR and high SNR.